Responding to nurses' communication challenges: Evaluating a blended learning program for communication knowledge and skills for nurses. Issue 7 (July 2022) - Kerr, Debra; Milnes, Sharyn; Martin, Peter; Ammentorp, Jette; Wolderslund, Maiken; Chiswell, Meg
Highlights: Blended teaching is an effective strategy for communication skills training. Flexibility is needed in professional development for work/life commitments. Theory and experiential learning improve nurses' knowledge and self-efficacy of communication. Nurses may lack micro-skills and knowledge of communication structure. Nurses find conversing with patients who have life-limiting illness challenging. Abstract: Objectives: To evaluate the effectiveness of the Blended Communication Skills Training Program for Nurses (CSTN). The program aims to improve nurses' knowledge about communication skills and structure for interactions with individuals who a have life limiting illness. Methods: This was a quasi-experimental study using a pre- and post-test quiz and self-efficacy questionnaire undertaken in Victoria, Australia. Nurses employed across three wards participated. The Blended CSTN comprised two major components: Asynchronous Web-Based Education Program and Experiential Workshop. The program focused on specific communication challenges: Gathering Information, Dealing with Difficult Questions, and Articulating Empathy. The primary outcome was improvement in knowledge of communication skills and structure. Self-efficacy and perceived importance of communication skills were assessed as secondary outcomes. Results: Eighteen nurses completed both Web-Based and Workshop components. Statistically significant increases in knowledge regarding communication skills and structure were found, with a large effect size for Gathering Information (r = 0.80) and moderate effect for Articulating Empathy (r = 0.62), and Responding to Difficult Questions (r = 0.532). Self-efficacy significantly increased for all measured communication skills. Conclusions: Knowledge improvements and perceived self-efficacy in communication were observed after nurses participated in a blended education program Practice implications: A blended CSTN may improve nurse-patient communication in the clinical setting, worthy of further study.